ANALISIS PENERAPAN ASAS GUGATAN KURANG PIHAK (PRULIUM LITIS CONSORTIUM) SEBAGAI ALASAN HAKIM MENOLAK GUGATAN WARIS (Studi Putusan Nomor 0735/Pdt.G/2015/PA.Bgr) - Jeri Ariansyah; Siti Rochmiatun; ifrohati ifrohati (Program Studi Al-Ahwal Al-Syakhshiyyah, 2021)
Religious Courts, as seeking justice for interested parties, in legal parties that are often encountered regarding war lawsuits. The judge is of the opinion that all heirs must be included in the inheritance lawsuit as subjects. In the case of inheritance, an error occurred in the investigation regarding the parties involved in the Religious Courts. an error in the inheritance lawsuit so that the lawsuit cannot be accepted by the judg(prulium litis consortium). Type of research library research, using a conceptual and legal approach. Types of data from qualitative data, legal materials: primary law, secondary law, and tertiary law. Qualitative descriptive analysis technique. The subject in the case of inheritance of decision 0735/Pdt.G/2015/PA.Bgr there are 3 heirs, parties in the case are only the first child as defendant, the third child as plaintiff. In addition, there are parties who should be included in lawsuit as co-defendants who control the inheritance because of the ownership rights by way of buying and selling between the first child as the seller, and the third party as buyer. application of the prulium litis consortium principle that judge has erroneously applied this principle so that the second heir who will be appointed as a co-defendant. Key words: Prulium Litis Consortium, Heirs, Religious Court